2012
DOI: 10.1371/journal.pone.0042282
|View full text |Cite
|
Sign up to set email alerts
|

β-D-glucan Surveillance with Preemptive Anidulafungin for Invasive Candidiasis in Intensive Care Unit Patients: A Randomized Pilot Study

Abstract: BackgroundInvasive candidiasis (IC) is a devastating disease. While prompt antifungal therapy improves outcomes, empiric treatment based on the presence of fever has little clinical impact. Β-D-Glucan (BDG) is a fungal cell wall component detectable in the serum of patients with early invasive fungal infection (IFI). We evaluated the utility of BDG surveillance as a guide for preemptive antifungal therapy in at-risk intensive care unit (ICU) patients.MethodsPatients admitted to the ICU for ≥3 days and expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 41 publications
0
66
0
7
Order By: Relevance
“…A single-centre study of twice-weekly BDG surveillance among high-risk ICU patients for >3 days reported a positive predictive value (PPV) of 30% for IC (sensitivity 100%, specificity 75%) with a negative predictive value (NPV) of 100%. 26 The study also found pre-emptive anidulafungin to be safe and associated with good outcomes. In light of more contemporary data, a re-evaluation of the role of BDG surveillance in Australia and New Zealand is warranted.…”
Section: ß(13)-d-glucan Detectionmentioning
confidence: 76%
“…A single-centre study of twice-weekly BDG surveillance among high-risk ICU patients for >3 days reported a positive predictive value (PPV) of 30% for IC (sensitivity 100%, specificity 75%) with a negative predictive value (NPV) of 100%. 26 The study also found pre-emptive anidulafungin to be safe and associated with good outcomes. In light of more contemporary data, a re-evaluation of the role of BDG surveillance in Australia and New Zealand is warranted.…”
Section: ß(13)-d-glucan Detectionmentioning
confidence: 76%
“…In the challenging scenario of early diagnosis of IC, recent studies have demonstrated the diagnostic value of BDG and CAGTA [19,[38][39][40][41][42]. Although the use of BDG measurement in daily practice for establishing the indication or the withdrawal of ESAT should be defined, recent observational studies [41,42] showed that negativity of the BDG assay may be used as a strategy to discontinue ESAT because of the high sensitivity and negative predictive value of the test.…”
Section: Invasive Candidiasismentioning
confidence: 99%
“…Preemptive ANF was nontoxic and often successfully tolerated with exceptional results. BG surveillance may be effectul in diagnosing ICU patients with a greater probability of developing IM [53].…”
Section: Advance Therapies For Better Treatment Strategies and Need Fmentioning
confidence: 99%